A call to ban non-essential microplastics used in cosmetics, festival and holiday decorations - Sara A.M. Silva; Joana C. Prata; Weiwei Zhang; Tony R. Walker (Cambridge Prisms: Plastics)
Festivities, holidays and celebrations are often associated with unsustainability and high environmental impact. Examples include unsustainable overconsumption and waste during Christmas, Ramadan and during the Chinese New Years celebrations among many others. Microplastics (i.e., plastic fragments 5 mm) have also become a significant environmental concern during these periods. Common non-essential festive items like glitter, confetti, balloons and other decorations along with glitter used in cosmetic products contribute to microplastic pollution, potentially causing adverse effects on ecosystems and human health. Despite overwhelming evidence of the adverse impacts of microplastics on human and environmental health, how non-essential microplastics used in cosmetics, festival and holiday decorations will be addressed within the Global Plastics Treaty remains unclear. Although the draft Global Plastics Treaty text includes non-essential plastic items such as balloons and rinse-off microbeads in cosmetics, no other decorative or aesthetic use of microplastics have been included. Whilst the inclusions of non-essential plastics are commendable, we argue that further inclusions be made for non-essential microplastics used in cosmetics, festival and holiday decorations within the Global Plastics Treaty.